Optimizing Expertise through Commercial Intellectual Property Achievement to Support Research Output Downstreaming: External Aspects in Policy Reform - R Benny Riyanto; Sucihatiningsih Dian Wisika Prajanti; Nurul Fibrianti; Karsinah Karsinah (Journal of Law and Legal Reform, 2024)
This study investigates the optimization of faculty expertise by leveraging commercial intellectual property (IP) achievements to facilitate the downstreaming of research outputs. It explores how universities can enhance their research impact and contribute to societal and economic development by effectively commercializing their intellectual assets. Emphasizing external aspects in policy reform, the research examines the intricate intersection of academia, industry, and legal frameworks. By aligning academic endeavors with policy reform initiatives, universities can create a conducive environment for knowledge transfer and innovation diffusion. This paper underscores the significance of integrating commercial IP achievements into academic practices to bridge the gap between research and real-world applications. Through strategic partnerships with industry and effective utilization of legal mechanisms, universities can maximize the commercial potential of their intellectual assets. Furthermore, by fostering a culture of innovation and entrepreneurship among faculty members, universities can drive impactful research outcomes that address societal challenges and fuel economic growth. The findings suggest that policymakers play a crucial role in shaping the regulatory landscape to incentivize and support commercialization efforts within academia. By implementing policies that streamline IP management processes and provide adequate funding and infrastructure support, governments can foster a vibrant innovation ecosystem that promotes collaboration between academia and industry. Ultimately, this study advocates for a holistic approach to research commercialization that integrates academic, industrial, and policy perspectives to maximize societal benefits and promote sustainable development.